2021
DOI: 10.1061/(asce)em.1943-7889.0001985
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Block-Based Simulation of Rocking Structures Using a Novel Universal Viscous Damping Model

Abstract: Unreinforced masonry structures, particularly façade walls, are seismically vulnerable due to their weak connections with adjacent walls, floors, and/or roofs. During an earthquake, such walls formulate local mechanisms prone to out-of-plane collapse. This behavior has been largely investigated using classical rocking theory, which assumes the structure responds as a rigid body undergoing rocking motion, with energy dissipation at impact. Due to the complexity of the problem, however, e.g., number of degrees o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 70 publications
(106 reference statements)
1
25
0
Order By: Relevance
“…Damping was treated as a dashpot applied at the nodes on the interfaces, reducing the velocity of the block, and a procedure similar to that proposed herein was adopted to correlate e and ζ n . Vlachakis et al 57 . found that the geometrical relationship h / b greatly influenced the relationship between e and ζ n , similar to the findings of the study reported here.…”
Section: Relationship Between Sp Rayleigh Damping and Coefficient Of ...supporting
confidence: 90%
See 4 more Smart Citations
“…Damping was treated as a dashpot applied at the nodes on the interfaces, reducing the velocity of the block, and a procedure similar to that proposed herein was adopted to correlate e and ζ n . Vlachakis et al 57 . found that the geometrical relationship h / b greatly influenced the relationship between e and ζ n , similar to the findings of the study reported here.…”
Section: Relationship Between Sp Rayleigh Damping and Coefficient Of ...supporting
confidence: 90%
“…Recently Vlachakis et al 57 . published a study expanding the research performed by Tomassetti et al 56 .…”
Section: Relationship Between Sp Rayleigh Damping and Coefficient Of ...mentioning
confidence: 94%
See 3 more Smart Citations